Penerapan CSR (Corporate Social Responsibility) Melalui Program Kemitraan dan Bina Lingkungan Oleh PT PLN (Persero) Tbk Wilayah Riau dan Kepulauan Riau Cabang Pekanbaru - Ferdian Septa; Firdaus '; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
CSR stands for Corporate Social Responsibility is the company's commitment to participate in the sustainable economic development to improve the quality of life and environment is beneficial, both for the company itself, the local community and society in general. Partnership Program which is a program to enhance the ability of small businesses to be strong and independent through the use of funds from the SOE profits annually. While Environment Development Program (, a program to establish prospective Partners new and empowering social conditions of society by the state through the utilization of funds from the profits of SOEs. When listened deeper, there is a difference between CSR private companies with CSR, state-owned company that implements CSR one of them PT PLN particularly PT PLN (Persero) Tbk Territory Riau and Riau Islands branch of Pekanbaru.Issues examined in this study are: First, Do the Partnership Program and Community Development (CSR) is included in the Corporate Social Responsibility (CSR)? Second, Do PKBL conducted by PT PLN (Persero) Tbk Territory Riau and Riau Islands Pekanbaru branch are in accordance with the provisions of Legislation in Indonesia ?? Third, What are the constraints and the efforts of PT PLN (Persero) Tbk Territory Riau and Riau Islands branch of Pekanbaru in the implementation of CSR?The results of this study are First In essence CSR is stipulated in the Regulation of the Minister of SOEs reserved for state-owned companies, so there will be an obligation for SOEs to implement CSR in the form of CSR, while CSR compulsory for all enterprises according to the Company Law, the Second Program Social Responsibility (CSR) through the Partnership by PT PLN (Persero) Tbk Territory Riau and Riau Islands branch Pekanbaru include Community Relations (Public Service), Community Services (Public Relations) and the Community Empowering (Independent Community), Third, efforts to overcome obstacles factor internal in the implementation of CSR through the CSR is to increase the number of human resources. Efforts undertaken by PT PLN to overcome external factors, namely to disseminate to the public, either directly or using electronic technology to inform about CSR through the CSR program conducted by PT PLN (Persero,Keywords: CSR - CSR - PT PLN (Persero)